2019
DOI: 10.1002/rcm.8464
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating temperature reconstructions from fish otolith oxygen isotope analysis for California's critically endangered Delta Smelt

Abstract: Rationale: Oxygen isotope ratios (δ 18 O values) of fish otoliths (ear bones) are valuable geochemical tracers of water conditions and thermal life history. Delta Smelt (Hypomesus transpacificus) are osmerid forage fish endemic to the San Francisco Estuary, California, USA, that are on the verge of extinction. These fish exhibit a complex life history that allows them to survive in a dynamic estuarine environment; however, a rapidly warming climate threatens this thermally sensitive species. Here we quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Sub-annual otolith δ 18 O values were measured by SIMS at the NordSIMS laboratory, Department of Geosciences at the Swedish Museum of Natural History in Stockholm, Sweden (Supplementary Table 2). SIMS is a probe-based method for determining the elemental and isotopic composition of solid materials (in otoliths: e.g., Darnaude et al, 2014;Helser et al, 2018;Willmes et al, 2019). Polished mounts were gold-coated, and the stable oxygen isotopes were measured using a CAMECA ims1280 ion microprobe, an advanced high-sensitivity mass spectrometer that uses a focused beam of ions to sample in situ selected micrometer-sized areas of a sample for measurement of isotopic composition.…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Sub-annual otolith δ 18 O values were measured by SIMS at the NordSIMS laboratory, Department of Geosciences at the Swedish Museum of Natural History in Stockholm, Sweden (Supplementary Table 2). SIMS is a probe-based method for determining the elemental and isotopic composition of solid materials (in otoliths: e.g., Darnaude et al, 2014;Helser et al, 2018;Willmes et al, 2019). Polished mounts were gold-coated, and the stable oxygen isotopes were measured using a CAMECA ims1280 ion microprobe, an advanced high-sensitivity mass spectrometer that uses a focused beam of ions to sample in situ selected micrometer-sized areas of a sample for measurement of isotopic composition.…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Therefore, the application of the equation for inorganic aragonite to chub mackerel would lead to errors in the estimation of their temperature experience, as suggested by previous studies (e.g. Kitagawa et al 2013;Sakamoto et al 2017;Willmes et al 2019). For example, suppose…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between ambient water temperature and otolith d 18 O has been quantified in various fish species and is often expressed using the following simplified formula: Kim et al (2007;see Kitagawa et al 2013;Sakamoto et al 2017). However, the constants obtained in the d 18 O analysis of several species differed slightly from those of the equation for inorganic aragonite (Kitagawa et al 2013;Sakamoto et al 2017;Willmes et al 2019). Several other studies have also suggested that the constants of temperature dependency equations differ among species (Høie et al 2004;Storm-Suke et al 2007;Godiksen et al 2010;Kitagawa et al 2013;Sakamoto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to recent analytical advances, it is now possible to measure stable isotopes with higher spatial/temporal resolution using secondary ion mass spectrometry (SIMS). This technique requires more preparation of the samples to be analysed [42], but in return offers a promising tool to unravel migration patterns and life history characteristics at much shorter timescales [43][44][45][46]. When water temperature and oxygen isotopic composition are known, it is possible to delineate isoscapes (i.e., spatial maps of predicted isotopic variation) that can be used to track potential movements across water masses with distinct isotopic signatures [47].…”
Section: Introductionmentioning
confidence: 99%